Arnold Beckman visit to East Germany - ADN Zentralbild (1973)
The photographs document meetings and tours in Germany. A number of the larger photographs bear the stamp of ADN Zentralbild. The inscription on the 7 in. x 5 in. photographs states that it was taken in Berlin. The inscription on the color photograph states that it was taken on April 5, 1973, in Dresden, and identifies the individuals with Arnold Beckman as Carl Kotchian (Lockheed) and Marvin Lewis (Ralph W. Parson Co.).
Keywords: Factories; Beckman, Arnold O.; Executives; Art museums; Meetings